Analisis Timbulan Limbah Medis Padat pada Puskesmas di Kabupaten Bantul - Arifah Wulansari; Sudarno Sudarno; Fuad Muhammad (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Wulansari A, Sudarno S, Muhammad F. 2020. Analysis of medical solid waste generation at puskesmas in Bantul Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Medical waste generation of puskesmas in Bantul Regency has continued to increase over the past 6 years (2014-2019), however, medical waste management at the puskesmas is still not optimally implemented due to limited availability of resources. The problem has become complex with the Covid 19 pandemic which is predicted will increase the quantity of hazardous waste that comes from medical services. This study aims to analyze medical solid waste generation at puskesmas in Bantul Regency during the Covid 19 pandemic by collecting primary and secondary data at 27 puskesmas. Data analysed using analytic descriptive techniques. The results showed that average generation of solid medical waste at puskesmas in Bantul district was 16.11 grams/patient.day for puskesmas rawat inap and 8.31 grams/patient.day for puskesmas rawat jalan. After the Covid 19 pandemic occurred in March 2020 there was an increase in the average generation of medical waste at 35.74 grams/patient.day for puskesmas rawat inap and 23.21 grams/patient.day for puskesmas rawat jalan. The results of statistical analysis showed that there was no correlation between number of patients and amount of medical waste produced at each puskesmas. However, number of patients correlated with rate of medical waste generation at each puskesmas with a pearson correlation value of -0.621. Strategy that can be taken to optimize medical waste management is carry out internal sterilization of waste before it is transported by a third party and improve the quality of TPS limbah B3 at the health center.